IMPLEMENTASI UNIFIED MODELING LANGUAGE DALAM PERANCANGAN APLIKASI MANAJEMEN ORGANISASI DHARMAYANA - Rizera Dwi Putri; Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Effective organization management is essential for achieving the goals of student organizations. Dharmayana, a student organization at Universitas Tarumanagara, faces challenges in managing member data, event planning, and equipment borrowing, which are still done manually. This study implements Unified Modeling Language (UML) in designing a web-based application to support Dharmayana's organizational management processes. Using Agile Scrum methodology, this research develops key UML diagrams, including use case, class, activity, and sequence diagrams, to capture and document system requirements comprehensively. The use case diagram identifies primary user roles—Owner, Admin, Inventory Manager, Member, and Visitor—ensuring each role’s functions are effectively mapped. The class and activity diagrams structure data and workflows, while the sequence diagram defines logical interactions within the system. This UML-based design provides a clear structure, supports data integrity, and enables the flexibility needed for system modifications. The results demonstrate that UML enhances the design process, making it more adaptable and efficient. This application model can serve as a reference for other student organizations aiming to streamline their management processes through technology.